A working research agenda for sports psychiatry <subtitle>Advancing evidence-based psychiatry in sport, exercise, and physical activity</subtitle> - Malte Christian Claussen; Alan Currie; James W. Burger; David Prossor; Ira Glick (Hogrefe AG, 2024)
Abstract: Introduction: Sports psychiatry is an emerging medical and psychiatric discipline that has experienced significant development in recent years. This growth has been accompanied by an increase in scientific outputs from sports psychiatrists and other academics that address the three fields of activity of sports psychiatry: namely, mental health and disorders in competitive and elite sports, mental health and sport-specific mental disorders in recreational sports, and the use of sport, exercise and physical activity in the prevention and treatment of mental disorders. Conceptual publications have discussed the scope of sports psychiatry and education and training. However, some topics receive more attention than others, with evidence gaps in other key areas of sports psychiatry. Advancing the field towards evidence-based practice requires an assessment of the current state of the literature and the development of a strategic research agenda. Methods: Following the Working Group on Research Gaps, Priorities and Agenda at the Summit on Sports Psychiatry arranged by the International Society for Sports Psychiatry (ISSP), the ISSP Scientific Committee conducted a narrative review of the sports psychiatry literature to benchmark the current academic state of the discipline and further developed the research agenda to provide a strategic framework for future research directions. Results: We discuss a research agenda according to five key areas: sports psychiatry as a discipline, education and training in sports psychiatry, and the three clinical fields of activity of sports psychiatry. Conclusion: This sports psychiatry research agenda provides a framework to guide the strategic development of the scientific literature in the field.